Antagonistic Bacillus cereus TC-1 Isolated from Solar Salt Work in Southern India (Bangladesh Journal of Microbiology, 2016)
Bacillus cereus TC-1 was isolated from condenser pond of manmade solar salt pan Thamaraikulam, Tamilnadu, India effectively suppressed the shrimp bacterial pathogens Vibrio harveyi, V. parahaemolyticus, V. anguillarum, V. alginolyticus and V. vulnificus by in vitro antagonistic assay of 9 to 15 mm of zone of inhibition. Phylogenetic analysis revealed that, B. cereus TC-1 was highly similar that the B. thuringiensis strain (100%) and other Bacillus sp. Their optimum growth between at the range of 4 to 6% of NaCl in the growth media and significantly (P